Effect of dietary exogenous phytase on laying performance of chicken at older ages (Bangladesh Journal of Animal Science, 2014)
A total of 48 Shaver-579 chicken layers aged between 85 to 94 weeks were reared in individual cages and given a basal diet amounting to 115g feed/bird/day. The basal diet fortified with 0.05, 0.10 or 0.15% Rena-Phytase-400 constituted of 3 experimental diets to see the effects of exogenous phytase on egg production and egg quality. Results indicated that increasing level of exogenous phytase in diet almost linearly (p